Կ․ Պոլսի պատրիարքարանի ներկայիս իրավիճակը - Անդրիկյան, Արման (ՀՀ ԳԱԱ Հնագիտության և ազգագրության ինստիտուտ)
Summing up we should say, that in the first chapter we spoke about the religious problems of Armenians in Turkey and about the policy led by Turkish government. Турецкое правительство проявляет неадекватное отношение к религиозным меньшинствам, что требует предпринять практические шаги по обеспечению их безопасности.
Keywords: International relations